Early Detection of Hypothermic Neuroprotection Using T2-Weighted Magnetic Resonance Imaging in a Mouse Model of Hypoxic Ischemic Encephalopathy - Doman, Sydney E.; Girish, Akanksha; Nemeth, Christina L.; Drummond, Gabrielle T.; Carr, Patrice; Garcia, Maxine S.; Johnston, Michael V.; Kannan, Sujatha; Fatemi, Ali; Zhang, Jiangyang; Wilson, Mary Ann (Frontiers in Neurology, 2018)
Perinatal hypoxic ischemic encephalopathy (HIE) can lead to neurodevelopmental disorders, including cerebral palsy. Standard care for neonatal HIE includes therapeutic hypothermia, which provides partial neuroprotection; magnetic resonance imaging (MRI) is often used to assess injury and predict outcome after HIE. Immature rodent models of HIE are used to evaluate mechanisms of injury and to examine the efficacy and mechanisms of neuroprotective interventions such as hypothermia. In this study, we first confirmed that, in the CD1 mouse model of perinatal HIE used for our research, MRI obtained 3h after HI could reliably assess initial brain injury and predict histopathological outcome. Mice were subjected to hypoxic ischemia (HI, unilateral carotid ligation followed by exposure to hypoxia) on postnatal day 7 (P7) and were imaged with T2-weighted MRI and diffusion-weighted MRI (DWI), 3 h after HI. Clearly defined regions of increased signal were comparable in T2 MRI and DWI, and we found a strong correlation between T2 MRI injury scores 3h after HI and histopathological brain injury 7 days after HI, validating this method for evaluating initial injury in this model of HIE. The more efficient, higher resolution T2 MRI was used to score initial brain injury in subsequent studies. In mice treated with hypothermia, we found a significant reduction in T2 MRI injury scores 3h after HI, compared to normothermic littermates. Early hypothermic neuroprotection was maintained 7 days after HI, in both T2 MRI injury scores and histopathology. In the normothermic group, T2 MRI injury scores 3h after HI were comparable to those obtained 7 days after HI. However, in the hypothermic group brain injury was significantly less 7 days after HI than at 3 h. Thus, early neuroprotective effects of hypothermia were enhanced by 7 days, which may reflect the additional 3 h of hypothermia after imaging or effects on later mechanisms of injury, such as delayed cell death and inflammation. Our results demonstrate that hypothermia has early neuroprotective effects in this model. These findings suggest that hypothermia has an impact on early mechanisms of excitotoxic injury and support initiation of hypothermic intervention as soon as possible after diagnosis of HIE.